IMPLEMENTASI PEMANFAATAN TIKTOK SEBAGAI MEDIA PEMASARAN EFEKTIF BAGI USAHA MIKRO, KECIL DAN MENENGAH (UMKM) STUDI KASUS SAHABAT BAKERI KAMAL - Anisa Nur Maulidiyah; Nur Laili Rahmawati; Savina Nur Lailiyah; Muhammad Alkirom Wildan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article discusses the utilization of TikTok as an effective digital marketing medium for Micro, Small, and Medium Enterprises (MSMEs), with a focus on the case study of Sahabat Bakery Kamal. In the midst of technological developments and changes in consumer behavior that are shifting to digital platforms, TikTok offers great opportunities for MSMEs to market products effectively. This research uses a qualitative approach involving interviews, observation, and documentation to analyze the marketing strategies implemented. The results show that the use of creative and interactive content, such as promotional videos and live streaming, can increase brand awareness and product sales, particularly Roti Roll Abon Madura. Nonetheless, MSMEs face challenges in maintaining content consistency and understanding the TikTok algorithm, which is necessary to reach a wider audience. This article recommends training to improve the digital skills of MSME players and the implementation of Customer Relationship Management (CRM) strategies to build better relationships with customers. With the right approach, TikTok can be a very potential tool to improve the competitiveness of MSMEs in an increasingly competitive market.